Penerapan Hasil Audit Keselamatan Jalan di Lokasi Rawan Kecelakaan Lalu Lintas - Gito Sugiyanto; Ari Fadli; Mina Yumei Santi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Traffic accidents are increasing along with the increasing number of traffic violations, the increasing number of vehicles, especially motorcycles, and driving vehicles exceeds the maximum allowable speed (speeding). The number of traffic accidents and the number of accident victims is increasing every year. Data from the National Police Traffic Corps, road transportation accidents in 2016 recorded 106,129 cases with 26,185 fatalities, 22,558 seriously injured, 121,550 minor injuries, and property damage only Rp 226,883,000,000.00. The most vulnerable road users are pedestrians, non-motorized vehicle users, children, and elderly people. The solution proposed is by mapping traffic accident-prone locations, conducting road safety audits at black spot locations to determine the conditions and handling efforts to reduce accident events in the form of installing traffic signs. The results of the road safety audit revealed that there had been a deficiency of road infrastructure in Tlahab Lor road section. One of the recommendations made is by installing traffic signs. Handling of black spot locations on the Tlahab Lor road, Karangreja that is by installing 4 (four) vehicle maximum limit signs of 40 km/h and 30 km/h. After knowing the location of black spot people is expected to be more alert and careful when passing through these roads.